Increased dimensional stability of alginate impression by addition cassava starch and sago starch - Risnayanti Anas; Syamsiah Syam (Makassar Dental Journal, 2020)
Background: Alginate impression material has a weakness about its dimensional stability being rapidly changing. Some na-tural ingredients contain polysaccharides namely amylose and amylopectin used to modify it. Comparison of amylose and ami-lopectin affects the degree of starch gelatinization; the greater the amylopectin content, the starch gel will be wetter, stickier and absorb less water. Objective: To determine the effect of the addition of cassava starch and sago starch to the dimensional stability of alginate impression. Method: Using a true experimental laboratory method with a cross-sectional design. Result: Based on the 1-way Anova test, the p-value was 0,000; smaller than 0.05. According to the post hoc multiple comparison test, the average difference between alginate plus cassava starch with controls was 0.35500, while alginate plus sago starch with controls was 0.75500. Conclusion: There is a significant change between the addition of cassava starch and sago starch to the dimen-sional stability of the alginate impression.